PERAN MARKET DAY DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN PESERTA DIDIK - Silvi Fitriyani; Khanah Nabilah; Sania Nur Izzati; Khusnul Khotimah (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Market Day is one of the experiential learning strategies designed to cultivate entrepreneurial values among students from an early age. This study aims to describe the role of Market Day activities in developing students’ entrepreneurial spirit and to explore the character values and skills that emerge through the implementation of these activities. The research employed a literature review method by analyzing various relevant scientific sources, including national and international journals discussing the application of Market Day in elementary and secondary schools. The findings show that Market Day plays a significant role in fostering students’ economic, social, and entrepreneurial skills. Through this activity, students learn to manage capital, set prices, market products, interact with customers, and take responsibility for their business outcomes. Furthermore, values such as creativity, honesty, discipline, self-confidence, and cooperation naturally develop throughout the process. Market Day also supports the implementation of the Pancasila Student Profile Reinforcement Project (P5) by teaching independence, collaboration, and practical problem-solving. In conclusion, Market Day is not merely a simple economic activity at school but serves as an effective contextual learning medium to shape students’ character and entrepreneurial mindset. Therefore, it is recommended that Market Day be continuously developed and integrated into the school curriculum as a strategic effort to prepare creative, competitive, and entrepreneurial-minded young generations.